A First-Principles Study on Hydrogen Sensing Properties of Pristine and Mo-Doped Graphene - Shulin Yang; Zhigao Lan; Huoxi Xu; Gui Lei; Wei Xie; Qibin Gu (Journal of Nanotechnology)
The adsorption of H2 on the pristine and Mo-doped graphene was investigated by density functional theory (DFT) calculations. The structural and electronic properties of H2-graphene systems were studied to understand the interaction between H2 molecule and graphene-based material. Our calculation results showed the pristine graphene was not an ideal sensing material to detect H2 molecule as it ran far away from the pristine graphene surface. Different with pristine graphene, the Mo-doped graphene presented much higher affinities to the H2 molecule. It was found that the placed H2 molecules could stably be chemisorbed on the Mo-doped graphene with high binding energy. The electronic property of Mo-doped graphene was significantly affected by the strong interaction and orbital hybridization between H2 and Mo-doped graphene sheet. The H2 molecule would capture more charges from the doped graphene than the pristine system, indicating the higher sensitivity for the graphene doped with Mo.